Bacteriocin producing Enterococcus faecalis isolated from chicken gastrointestinal tract originating from Phitsanulok, Thailand: Isolation, screening, safety evaluation and probiotic properties. (August 2017) - Hwanhlem, Noraphat; Ivanova, Teodora; Biscola, Vanessa; Choiset, Yvan; Haertlé, Thomas
Abstract: A total of 230 isolates of lactic acid bacteria were isolated from gastrointestinal tracts (GIT) of indigenous chickens purchased from local market in Bang Rakam district, Phitsanulok, Thailand. Among 230 isolates, only 7 isolates, named CM6CR07, CM6CR11, CF1GI15, CF1GI14, CF1GI17-1, CF1GI17-2 and CF1GI 19 showed an inhibition zone against indicator strains. Bacteriocin activity was completely inactivated when Neutralized Cell Free Supernatants (NCFS) of the isolates were treated with proteases, confirming the proteinaceous nature of the bacteriocin component. NCFS of all selected bacteriocin producing lactic acid bacteria (SBP-LAB) retained their bacteriocin activity after heating at 100 °C for 30 min. All of SBP-LAB were identified as Enterococcus faecalis . These Ent . faecalis isolates harbored the same virulence genes. All strains were positive for gel E (gelatinase), efa Afs (cell wall adhesins), hyl (hyaluronidase), ace (adhesin of collagen protein), cyl LL (cytolysin structural subunit) and cyl LS (cytolysin structural subunit) and were negative for asa1 (aggregation substance), agg (aggregation protein involved in adherence to eukaryotic cells), and esp (enterococcal surface protein). These Ent . faecalis showed a wide range of inhibitory spectrum against food-spoilage and food-borne pathogens when studied by agar spot test. The CFS and NCFS also inhibited some of food-spoilage and food-borne pathogenic indicator strains when checked by agar well diffusion assay. All of these Ent . faecalis survived simulated stomach conditions, whereas all of them could survive in conditions of simulated intestinal juice. Highlights: Bacteriocin producing Enterococcus faecalis was isolated from chicken GIT. Bacteriocin producing Ent . faecalis harbor virulence genes. Ent . faecalis showed activities against food-spoilage and food-borne pathogens. Ent . faecalis present a potential for their application as biocontrol agents.